1995
DOI: 10.1159/000227418
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of CD4 Antigen Expression on the Lymphocyte Surface by Immunosuppressive Acidic Protein in Cancer Patients

Abstract: The immunomodulatory effect of human immunosuppressive acidic protein (IAP) on lymphocyte surface antigens was investigated. IAP inhibited lymphocyte responses to phytohemagglutinin in a dose-dependent manner. By flow cytometry, using fluorescein-isothiocyanate-labelled antibodies, the mean fluorescence intensity on peripheral blood lymphocytes (PBLs) decreased for CD4, slightly decreased for CD3 but showed no change for the CD8 and T cell receptor a-(3 antigens in the presence of IAP. This CD4 antigen modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Surgical stress induces the release of cytokines such as TNF-伪, IL-1, IL-6 and IL-8 from the operated site or the damaged tissues. IL-6 is the main mediator of the host acute phase responses, and stimulates hepatocytes to produce acute phase reactants such as immunosuppressive acid protein (IAP), C-reactive protein (CRP), and others [ 20 , 21 ]. IAP is reported to modulate the CD4 antigen expression by lymphocytes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical stress induces the release of cytokines such as TNF-伪, IL-1, IL-6 and IL-8 from the operated site or the damaged tissues. IL-6 is the main mediator of the host acute phase responses, and stimulates hepatocytes to produce acute phase reactants such as immunosuppressive acid protein (IAP), C-reactive protein (CRP), and others [ 20 , 21 ]. IAP is reported to modulate the CD4 antigen expression by lymphocytes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is the main mediator of the host acute phase responses, and stimulates hepatocytes to produce acute phase reactants such as immunosuppressive acid protein (IAP), C-reactive protein (CRP), and others [ 20 , 21 ]. IAP is reported to modulate the CD4 antigen expression by lymphocytes [ 21 ]. Therefore, the increase in IL-6 levels after small intestinal resection might be one of the factors that suppress lymphocyte function, such as CD4+ T cell depletion or a shift to Th2.…”
Section: Discussionmentioning
confidence: 99%
“…IAP has been reported to be a member of the 路1-acid glycoprotein family (19). IAP also has been demonstrated to down-modulate CD4 molecules on the lymphocyte surface, leading to the establishment of cancer-associated immunodepression, and to induce suppressor-inducer cells (20). Con-A-induced suppressor cell activity has been reported to indicate the presence of suppressor precursor cells that mature in response to stimulation with suppressor inducer cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…IAP has been shown to impair phytohemagglutinininduced lymphocyte blastogenesis and the 2-way mixedlymphocyte reaction (Tamura et af., 1981). The induction of suppressor macrophages by IAP was demonstrated in mice, and it has been shown that IAP leads to down-modulation of CD4 antigen on human lymphocytes (Yamaguchi et al, 1995).…”
mentioning
confidence: 99%